Simultaneous Presentation of Gastric and Orbital Mucosa‐Associated Lymphoid Tissue Lymphoma: A Case Report - Elahe Mirzaee; Maryam Garousi; Shima Jafari; Sepideh Soltani; Nasser Rakhshani; Navid Abdi; Pedram Fadavi (Clinical Case Reports)
ABSTRACT Mucosa‐associated lymphoid tissue lymphoma or MALToma occurs in 8% of B‐cell non‐Hodgkin lymphoma according to the latest WHO classification. The most involved site of MALToma is stomach. We describe a rare case of concurrent gastric and orbital mucosa‐associated lymphoid tissue lymphoma (MALToma) of a female who presented with progressive proptosis and abdominal pain. We performed six courses of chemotherapy (Rituximab) and gastric and orbital radiation with a dose of 34 Gy/20 Fr and 30 Gy/20 Fr, respectively. This case underscores the efficacy of a multimodal treatment strategy in achieving successful outcomes.